Research on Academic English Abroad and Its Implications for the Instruction of Academic English Writing in China - Qu, Qiong; Yu, Linger (Journal of Educational Research and Policies, 2026)
This study draws on journal articles related to academic English research indexed in the Web of Science database from 2000 to 2025 as its data source. A systematic review and analysis are conducted to show the developmental trends and current state of research in this field internationally. In addition, pedagogical implications for academic English writing instruction in China are proposed in light of the domestic teaching context. The findings indicate that research on academic English writing has gradually shifted from a primary focus on language form to a broader concern with cognitive processes, disciplinary discourse practices and writing support tools. In particular, increasing attention has been directed toward the impact of Gen-AI on academic writing and its instruction. Accordingly, it is argued that academic writing instruction in China should adopt human-AI collaboration as its core orientation, strengthening the development of learners’ cognitive abilities while regulating the use of Gen-AI and guiding its appropriate integration into writing practice.